ROLE OF HISTORY IN VLADIMIR PUTIN’S FOREIGN POLICY STRATEGY - O. N. Barabanov (Vestnik MGIMO-Universiteta, 2016)
The subject of the article is dedicated to the evolution of the visible accent on the role of history and historico-civilizational heritage in formulation of Russia's foreign policy strategy in conceptual speeches of the President of Russia Vladimir Putin in 2013-2015. His thesis on Russia as a country-civilization, proclaimed in Summer-Autumn 2013, became the basis for serious practical steps for activization of the foreign policy of Russia starting from 2014. It became clear mainly during the Ukrainian crisis, but also other key international events of the last two years. Another significant element of such a strategy was the thesis on the sacrality of history for Russia, exceeding far beyond a traditional focus on using the historical memory in current politics, that one can see in other states' examples. The consequence of that thesis is the feeling of specific historical responsibility in front of Russia for state politicians, also formulated by President Putin. All this could be considered as a new dimension of the moral basis of politics. One more focus of the article is on the role of new public political panels for proclaiming such a historically motivated politics, like the Valdai Discussion Club, etc.